2001
DOI: 10.1097/00004647-200112000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetazolamide on Cerebral Blood Flow, Blood Volume, and Oxygen Metabolism: A Positron Emission Tomography Study with Healthy Volunteers

Abstract: To evaluate changes in cerebral hemodynamics and metabolism induced by acetazolamide in healthy subjects, positron emission tomography studies for measurement of cerebral perfusion and oxygen consumption were performed. Sixteen healthy volunteers underwent positron emission tomography studies with 15O-gas and water before and after intravenous administration of acetazolamide. Dynamic positron emission tomography data were acquired after bolus injection of H2[15O] and bolus inhalation of 15O2. Cerebral blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
101
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 27 publications
9
101
0
Order By: Relevance
“…18 The administration of ACZ may shorten the arrival time as a result of increased blood velocity and aid early influx of labeled water into the brain tissues, which may enhance ASL signals with a short PLD preferentially and consequently cause overestimation of CVR. The mean CVR values reported in normal subjects range from 25-31% with the use of 133 Xe inhalation SPECT, 18,21-23 from 33.5-35% with the use of 15 O-water positron-emission tomography, 24,25 and from 37.7-54.2% with the use of ASL MR imaging. [9][10][11] Although the CVR values obtained with the use of a PLD of either 1525 ms (43.8 -46.4%, depending on the region) or 2525 ms (26.9 -32.5%) in the present study are in the range of the reported values, those obtained with a PLD of 1525 ms as well as those previously reported by use of ASL MR imaging are relatively high; thus, ASL MR imaging probably leads to overestimation of CVR.…”
Section: Discussionmentioning
confidence: 96%
“…18 The administration of ACZ may shorten the arrival time as a result of increased blood velocity and aid early influx of labeled water into the brain tissues, which may enhance ASL signals with a short PLD preferentially and consequently cause overestimation of CVR. The mean CVR values reported in normal subjects range from 25-31% with the use of 133 Xe inhalation SPECT, 18,21-23 from 33.5-35% with the use of 15 O-water positron-emission tomography, 24,25 and from 37.7-54.2% with the use of ASL MR imaging. [9][10][11] Although the CVR values obtained with the use of a PLD of either 1525 ms (43.8 -46.4%, depending on the region) or 2525 ms (26.9 -32.5%) in the present study are in the range of the reported values, those obtained with a PLD of 1525 ms as well as those previously reported by use of ASL MR imaging are relatively high; thus, ASL MR imaging probably leads to overestimation of CVR.…”
Section: Discussionmentioning
confidence: 96%
“…Because V a includes the blood volume of cerebral arterioles, our results correspond well to these previous observations. In addition, an increase in V a during acetazolamide stress has also been observed in human brain (Okazawa et al, 2001). V c is considered to be negligibly small (Mintun et al, 1984); however, V c in the living human brain is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2. Because the exponential term in Grubb's power law relating flow to blood volume is less than 1, the finding that acetazolamide alters CBF more than CBV (Okazawa et al, 2001) implies that acetazolamide administration would reduce M, causing %BOLD to decline. The restricted dynamic range account of the relationship between %BOLD and resting perfusion explains the diminished BOLD response as a result of a floor effect for deoxyhemoglobin concentration under conditions of high resting CBF.…”
Section: Discussionmentioning
confidence: 99%